2020
DOI: 10.1002/solr.202000282
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Type‐II 2D/3D Perovskite Heterojunctions for Enhanced Stability and Photovoltaic Efficiency

Abstract: The energy demand is rapidly increasing for the increased population and the improved life quality. [1] Disafforestation or mining will destroy the ecological balance and even bring some unknown diseases, which will kill thousands of people. Thus, an environmentally friendly method to obtain energy is necessary and urgent. Solar energy is a kind of clean and abundant energy, which can be harvested conveniently. Nowadays, silicon solar cells are dominant in the solar energy industry, but we need more cost-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In addition, a hydrophobic 2D ultrathin perovskite layer can improve the humidity stability of the PSCs. It was reported that by using this method, a PSC maintained an initial efficiency of 80% for 350 h at 70–80% relative humidity [ 89 ]. Meanwhile, Wang et al utilized the amphiphilic structure of large molecule S-benzyl-L-cysteine and its unique solubility behavior.…”
Section: Interface Modificationmentioning
confidence: 99%
“…In addition, a hydrophobic 2D ultrathin perovskite layer can improve the humidity stability of the PSCs. It was reported that by using this method, a PSC maintained an initial efficiency of 80% for 350 h at 70–80% relative humidity [ 89 ]. Meanwhile, Wang et al utilized the amphiphilic structure of large molecule S-benzyl-L-cysteine and its unique solubility behavior.…”
Section: Interface Modificationmentioning
confidence: 99%
“…Though the CBM of 2D perovskite is slightly lower than that (−4.3 eV) of PC 61 BM (see Figure a), , the electron transport may not be hindered due to the electron tunneling effect . Nevertheless, the hole transport toward ETL could be efficiently blocked due to the deeper VBM (−6.8 eV) of 2D perovskite with respect to that (−5.9 eV) of PC 61 BM, which might fundamentally account for the improved V OC . , Herein, the role of the 2D/3D structure is very different from those in regular (p–i–n) PSCs, where the as-formed 2D/3D structures promote the hole transfer and block the electron transfer. , …”
Section: Resultsmentioning
confidence: 93%
“…36,37 Herein, the role of the 2D/3D structure is very different from those in regular (p−i−n) PSCs, where the as-formed 2D/3D structures promote the hole transfer and block the electron transfer. 17,18 Moreover, to quantitatively estimate the trap densities in the CsPbI 2 Br perovskite film without and with the posttreatment, trap-filled limit (TFL) current model 46 was applied for the electron-only devices (EODs) with a configuration of ITO/ PC 61 BM/PVK/PC 61 BM/Ag. Dark J−V curves of EODs are provided in Figure 5b, showing an SCLC regime where the kink point voltage is determined as TFL voltage (V TFL ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations